Providing Justice To Women In Conflict With The Law - Rohman, Syaiful; Hawadi, Lydia Freyani; Batubara, Ika Arini (Westscience Press, 2025)
The principle of justice is the main foundation that must be upheld regardless of gender, race, or social background. However, in reality, women in conflict with the law often face different challenges and discrimination compared to men. It must be recognized that women are vulnerable in the legal and social context. They often experience structural and cultural inequalities, which can affect their access to justice. For example, negative perceptions and gender stereotypes sometimes affect the objectivity of law enforcement officials in handling cases involving women, both as victims and suspects. Therefore, providing justice to women in the legal process is a necessity that is not only normative but must also be realized in real terms through special policies, approaches, and protection. This article analyzes how gender-responsive legal protection and assistance mechanisms are crucial for women dealing with the law. This research uses descriptive qualitative methods to gain an in-depth understanding of the problems faced by women in the legal process. The results showed that providing justice to women in conflict with the law requires a real commitment from various parties, from law enforcement agencies and legal counsel through mechanisms to strengthen advocacy and gender mainstreaming. Thus, justice can be felt and given without gender discrimination, and women can be protected, treated fairly, and have their rights by applicable regulations.